Alternativas al problema de la basura en el barrio catedral de la ciudad de encarnación (Journal on studies and research of academic knowledge, 2010)
The environment has among its fundamental functions: to be a supplier of production goods in the form of materials or energy,act as source of wellness and leisure services and a sump for the waste materials created as a result of the economic activity.The residue or waste component appears as something without value in use, and therefore value change.  The economic importance of waste management has become more and more patent in recent years as a solution to the problem that must be faced from all fronts: collective and individual, through policies and management plans and their effective implementation by education and participation of the population to these tools.This investigation, define the need (or not) for the modification of the collect system and Final Treatment for the solid waste in a neighborhood of the city of Incarnation, the Cathedral Quarter.This investigation is Descriptive, as in it was research to define the important properties of the studied element, explained how it is and it´s behavior.As a result it was achieved that is possible the modification of the collect system of the waste, working in the previous separation with satisfactory results.The interviewed Families show a high acceptation for the implementation of a site of separation system in the houses, toallow the implementation in the waste storage site of a recycle system to achieve a reduction of the volume of the disposed wastes.We conclude the viability of the implementation a plan of collection and sorting of waste and a landfill.
Keywords: Environment; Waste; Management